Development and Cost-Effectiveness Analysis of a Fogging Pump Control System Commercial Prototype for Oyster Mushroom Cultivation based on Open-System Greenhouse - Pinngern, Non; Wanganusorn, Bhannawat (Journal of Applied Informatics and Technology, 2025)
This study proposes a commercial development model for a fogging pump control system (FPCS) for oyster mushroom cultivation in open-system greenhouses, which are the most common type of greenhouses used for mushroom cultivation in Thailand. A prototype system was developed using a commercially available controller that was modified to make it easier to produce in large quantities. The system was designed with two separate components: The first component controlled the operation of the fog pump by alternating between spraying and pausing to maintain the desired humidity. It also acted as an access point to release a Wi-Fi signal that allowed users to access the system settings via a website. The second component was installed in the mushroom greenhouse and sent weather data from sensors to the first component via Wi-Fi. The whole system does not require internet usage. The prototype system was tested in an oyster mushroom greenhouse for 60 days. The results showed that the system was easy to install and operate in commercial mushroom farms. It was also effective in controlling humidity for oyster mushroom cultivation. An economic analysis of the system showed that it could help farmers to reduce unit costs by up to 72.30%. The system also had a positive net present value (NPV) of +332,600, an internal rate of return (IRR) of 281%, and a payback period of one production cycle (2 months). These results suggest that the proposed FPCS is suitable for commercial production for controlling humidity in oyster mushroom cultivation in open-system greenhouses.